The role of internet self-efficacy, innovativeness and technology avoidance in breadth of internet use: comparing older technology experts and non-experts - Jokisch, Mario; Schmidt, Laura; Doh, Michael; Marquard, Markus; Wahl, Hans-Werner (Computers in human behavior, 2020)
Older adults show pronounced interindividual differences in terms of their technology adoption, experiences and resources. To better understand this heterogeneity, we compared older technology experts and non-experts. We focused on General Internet self-efficacy (GISE) and Communication related Internet self-efficacy (CISE). Further, we considered innovativeness and technology avoidance as variables able to predict GISE and CISE, which we assumed to be related to two different areas of Internet use (informational, communication and instrumental). Samples included 131 older technology experts engaged as volunteer coaches in government-supported technology projects (age: M = 68 years; range = 50-88 years; 33% female) and 239 older adults with no technology expertise (age: M = 72 years; range = 57-87 years; 61% female). All subjects completed a paper-pencil or online questionnaire containing established measures of study constructs. Multigroup structural equation models revealed that innovativeness was an important predictor of GISE and CISE in both groups, whereas technology avoidance was related only to GISE in the expert group. Further, higher GISE was more strongly linked to informational Internet activities in non-experts than in experts, while CISE was related to communication and instrumental Internet activities in both groups. Findings support our expectation that conceptually distinct Internet relevant constructs play a differential role depending on expert status of older technology users.